Pemberdayaan Pemandu Lingkungan melalui Workshop Persiapan Katekese: Implementasi Model Pembelajaran Transformatif di Paroki Santo Krisologus BSB Semarang - Stepanus Istata Raharjo; Anselmus Joko Prayitno; Nerita Setiyaningtiyas (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
This community service program aims to enhance the competence of community facilitators in implementing catechesis at Santo Krisologus BSB Parish Semarang. Based on preliminary studies, fundamental problems were identified, including deficiencies in facilitative competencies and disparities in community participation in catechetical activities. The workshop was designed using a multi-dimensional methodological approach integrating Mezirow's transformative learning theory and Groome's shared Christian praxis model. The program was conducted on October 20, 2024, with the participation of 34 novice community facilitators. The workshop implementation involved three main components: theoretical material presentation, guided practicum, and learning community formation. Results showed significant improvements in participants' theoretical understanding and practical skills, particularly in participative, appreciative, and reflective dimensions. The formation of learning communities indicates potential program sustainability through peer learning mechanisms. This program contributes to the renewal of community catechesis aligned with the vision of Church ad extra and can serve as a prototype for developing similar programs in other parishes.